Analisis Struktur Skeleton Embrio Kadal (Mabouya multifasciata) dengan Pewarnaan Alizarin Red - Nur Khasanah; Hari Santoso; Ratna Djuniwati Lisminingsih (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2020)
The bone growth on any organisms have different patterns and equity. In the embryo of ossification lizards happened it during the eggs in the body of the parent before was born. The research aim is to find a bone structure of the embryo that was 48 days old. The method used qualitative with the technique of purposive sampling and alizarin red staining. Using the six embryos of lizards (mabouya multifasciata) and it was taken directly from the mother. The analysis used is counting the long of vertebrae and extremitie. The obtained results were the red colur on limb and vertebrae. Sections of the anterior extremity which undergoes ossification is the humerus, radius, the ulna, phalanges and claws. The posterior extremity which ossification is the femur, the fibula, the tibia, phalanges and claws. The vertebrae bone that it hapened ossification was cervical vertebrae , vertebrae thoracic, lumbar vertebrae , sacralis vertebrae and caudalis vertebrae. Whereas a bone in the part of the limb posterior ones which are not hapened ossification is the carpal and metacarpal. Keywords : lizard, alizarin red, bone structure ABSTRAK Struktur pertumbuhan tulang pada setiap masing-masing organisme mempunyai pola berbeda dan persamaan. Pada embrio kadal osifikasi terjadi semasa fase telur dalam tubuh induk sebelum dilahirkan. Tujuan penelitian untuk mengetahui struktur tulang embrio berumur 48 hari. Metode penelitian menggunakan kualitatif dengan teknik pengambilan sampel purposive sampling dan pewarnaan alizarin red. Menggunakan embrio kadal (Mabouya multifasciata) sebanyak enam ekor diambil langsung dari perut induknya. Analisis adalah menghitung panjang tulang vertebrae dan ekstremitas. Hasil yang telah didapat adalah tulang ekstremitas dan vertebrae yang telah berwarna merah. Bagian tulang ekstremitas anterior yang telah terosifikasi adalah humerus, radius, ulna, falang dan cakar. Pada tulang ekstremitas posterior yang sudah mengalami osifikasi adalah femur, fibula, tibia, falang dan cakar. Tulang vertebrae yang sudah mengalami osifikasi adalah vertebrae servikalis, vertebrae torakalis, vertebrae lumbalis, vertebrae sacralis dan vertebrae caudalis. Sedangkan tulang di bagian ekstremitas posterior yang belum mengalami osifikasi yaitu carpal dan metacarpal. Kata Kunci : kadal, alizarin red, struktur tulang